Standalone hybrid power system using homer software optimal case sizing of ferraguig (North West of Algeria) - B. Afif; B. Merabet; A. Benhamou; A. Chaker (International Journal of Applied Power Engineering (IJAPE), 2019)
Rural areas suffer from high costs of grid extensions obliging institutions to provide for other remedies for consumers, like using generators (GE) diesel often considered as economic and reliable solutions, but at the detriment of some order environment pollution and users convenience. Furthermore, the continuous decline in GEs prices based on a renewable energy (RE) and the increasing reliability of these systems have lead to a greater use of renewable energy sources for power generation in remote areas. A property which limits the use of renewable energy is related to the variability of resources. Fluctuations in load according to annual or daily periods are not necessarily correlated to the resources. In remote areas, the preferred option is the coupling between multiple sources, such as wind turbines and solar panels, this coupling is called hybrid power system. Algeria’s geographic location presents several advantages for the development and use of renewable energy, namely, solar energy and wind energy. In addition, Algeria has huge deposits of natural gas, 98% electricity comes from gas. Therefore, currently, the production of electricity from renewable energies primarily depends on their competitiveness with economic gas. Studied technological feasibility and economic viability of the hybrid system (PV/fuel) electrification project in a school located in Ferraguig succeed to reduce high costs, energy dependence, fuel supply problem, complicated/expensive maintenance, low lifetime, impossibility of 24 hours electricity production and waste oil management issues, by using renewable energy. HOMER model is used here to size a proposed system and determine an optimum configuration.